PENGEMBANGAN PRODUK MELALUI DESAIN KEMASAN UNTUK MENINGKATKAN MINAT BELI PADA BANGI CAFE SUNSET CPI - Rachmat, Adiva; Sayuti, Nuraeni (ADMIT: Jurnal Administrasi Terapan, 2024)
The Food and Beverage (F&B) sector has a very important role in the economy, both globally and at the domestic level. One way to improve   product buying interest in the Food and Beverage sector is by developing new products. Product development is the process of creating goods and services to adjust the products made or offered for sale in accordance with consumer demand. In this study, product development will be carried out through packaging design. Bangi Cafe Sunset is a cafe that has a classic concept. Bangi Cafe Sunset is located at Metro Tanjung Bunga Street No. 18 Center Point of Indonesia, Mariso District, Makassar City, South Sulawesi. The purpose of this study is to develop packagedesign for products in Bangi Cafe Sunset CPI to increase buying interest by adding product identity to the packaging. The method of the study is a qualitative method by observing and interviewing. The results of this research show that the development of the new packaging design for Bangi Cafe Sunset was carried out through six stages of product development and Bangi Cafe Sunset improves  its packaging from the plain brown kraft packaging to the color of the ivory material with the design based on the results of the consumer interview and the agreement of the owner of Bangi Cafe Sunset and the Central Manager of Bangi Cafe to attract consumer buying interest.